Literary Copyright - Warner, Charles Dudley, 1829-1900 (Salt Lake City, UT : Project Gutenberg, 2004)
"Literary Copyright" by Charles Dudley Warner is a scholarly exposition focused on the rights and interests surrounding literary works, likely written during the late 19th century. This book addresses the critical need for better copyright laws that protect authors, publishers, and the public in their creative and commercial relationships. Its central theme revolves around advocating for more robust and just copyright protections for authors and establishes its discussion on the intrinsic value of intellectual property. In "Literary Copyright," Warner emphasizes the importance of recognizing an author's right to their creations, arguing that copyright laws should provide authors with full ownership of their works rather than restricted periods of control. He critiques the existing copyright system, highlighting how it favors publishers and commercial interests over the original creators. Warner addresses the complicated dynamics between authors and publishers, advocating for a fairer contract structure that supports literary excellence and encourages the production of quality literature. He insists that the relationship between authors and their audience should value artistic integrity above commercial exploitation, reflecting on the potential harm that a market-driven approach to writing can inflict on literary quality and culture as a whole. (This is an automatically generated summary.)
Release date is 2004-12-05
Produced by David Widger
Keywords: Copyright